Application of Digital Literacy for Adolescents in SMA Negeri 1 Gamping - Iis Lathifah N; Drajat Edy Kurniawan; Anggi Sulistiyantoro; Aida Nur Asyifa; Septia Nadia Virani (CV. Rayyan Dwi Bharata, 2023)
A service study entitled Application of Digital Literacy for Youth in SMA Negeri 1 Gamping. The adolescent development phase of high school age students is in middle adolescence, namely at the age of 15-18 years. Most internet users are teenagers. Community Service was carried out at SMA Negeri 1 Gamping on November 16 2022. Based on a preliminary study by analyzing the needs of students in high school, namely the need for a more detailed understanding of digital literacy. The activities of students in using the internet need more attention. This is the background for holding a Seminar on Digital Literacy for teenagers. The provision of information about digital literacy is expected to have a positive influence on adolescent students, especially teenagers.